Expansion of cardiac ischemia/reperfusion injury after instillation of three forms of multi-walled carbon nanotubes - Urankar, Rakhee N; Lust, Robert M; Mann, Erin; Katwa, Pranita; Wang, Xiaojia; Podila, Ramakrishna; Hilderbrand, Susana C; Harrison, Benjamin S; Chen, Pengyu; Ke, Pu Chun; Rao, Apparao M; Brown, Jared; et al. (My University, 2012)
Background The exceptional physical-chemical properties of carbon nanotubes have lead to their use in diverse commercial and biomedical applications. However, their utilization has raised concerns about human exposure that may predispose individuals to adverse health risks. The present study investigated the susceptibility to cardiac ischemic injury following a single exposure to various forms of multi-walled carbon nanotubes (MWCNTs). It was hypothesized that oropharyngeal aspiration of MWCNTs exacerbates myocardial ischemia and reperfusion injury (I/R injury). Methods Oropharyngeal aspiration was performed on male C57BL/6J mice with a single amount of MWCNT (0.01 - 100 μg) suspended in 100 μL of a surfactant saline (SS) solution. Three forms of MWCNTs were used in this study: unmodified, commercial grade (C-grade), and functionalized forms that were modified either by acid treatment (carboxylated, COOH) or nitrogenation (N-doped) and a SS vehicle. The pulmonary inflammation, serum cytokine profile and cardiac ischemic/reperfusion (I/R) injury were assessed at 1, 7 and 28 days post-aspiration. Results Pulmonary response to MWCNT oropharyngeal aspiration assessed by bronchoalveolar lavage fluid (BALF) revealed modest increases in protein and inflammatory cell recruitment. Lung histology showed modest tissue inflammation as compared to the SS group. Serum levels of eotaxin were significantly elevated in the carboxylated MWCNT aspirated mice 1 day post exposure. Oropharyngeal aspiration of all three forms of MWCNTs resulted in a time and/or dose-dependent exacerbation of myocardial infarction. The severity of myocardial injury varied with the form of MWCNTs used. The N-doped MWCNT produced the greatest expansion of the infarct at any time point and required a log concentration lower to establish a no effect level. The expansion of the I/R injury remained significantly elevated at 28 days following aspiration of the COOH and N-doped forms, but not the C-grade as compared to SS. Conclusion Our results suggest that oropharyngeal aspiration of MWCNT promotes increased susceptibility of cardiac tissue to ischemia/reperfusion injury without a significant pulmonary inflammatory response. The cardiac injury effects were observed at low concentrations of MWCNTs and presence of MWCNTs may pose a significant risk to the cardiovascular system.
Keywords: Pulmonary exposure, BAL, Serum cytokines, Modified carbon nanotubes, MWCNT, Nanotoxicology, Nanoparticle